The Politics Hurdle: Joint Effect of Organizational Culture and Gender on Lack of Fit Experiences. Issue 1 (January 2023) - Salwender, Mona; Schoel, Christiane; Bless, Herbert; Stahlberg, Dagmar
We propose that an organizational culture where playing politics is important for advancement, compared with an organizational culture where showing competencies is important, elicits stronger lack of fit experiences for women than for men. In a pre-study, playing politics was perceived as dominant, typically male work behaviors, whereas showing competencies was perceived as competent, typically female work behaviors. We then tested in two experiments (689 individuals, integrated in a small-scale meta-analysis) the joint effect of organizational culture and gender on four lack of fit indicators (self-concept conflict, fear of backlash, intention to seek power positions, concerns about one's skills). As expected, women indicated more lack of fit experiences than men in politics cultures, but not in competencies cultures. Our findings suggest that perceived organizational culture may play an important role in understanding the dynamics of career advancement of women and men.